Identification and expression characterization of apple β-tubulin gene family in apple - HUANG Huiling; WANG Yanxiang; WANG Yue; NING Qinqin; LI Ming; HAO Pengbo; CONG Liu; BAI Tuanhui; SHI Jiangli; JIAO Jian; WANG Miaomiao; LIU Yu; et al. (Guoshu xuebao)
[Objective] Microtubule is composed of α-and β-tubulin heterodimers. It is known that α- and β-tubulins are encoded with large family genes and selected expression of α-and β-tubulin family genes plays key roles in regulating various biological processes, including plant growth and development, stress responses and signaling transduction. However, little is known about apple tubulin family genes and their potential functions. Therefore, the present study was to identify the apple β-tubulin family genes and to determine the candidate β-tubulin genes involved in regulating apple dwarfing. [Methods] Using Arabidopsis thaliana β-tubulin amino acid sequences as reference, apple β-tubulin family genes were identified from the apple reference genome GDDH13 v1.1. In the following, bioinformatic analysis was conducted to dissect the physicochemical properties, chromosome localization, phylogenetic relationships, gene structure, conserved motifs, collinearity, three-dimensional structure prediction and cis-acting elements in their promoter regions of the identified apple β-tubulin family genes. Different tissues including mature and young leaves, xylem, phloem and stem tips of column apple Runtai No.1 were collected as materials to analyze the tissue expression patterns of apple β-tubulin family genes through quantitative real-time PCR (RT-qPCR). To screen the candidate β-tubulin genes involved in regulating apple dwarfing, the relative expressions of apple β-tubulin family genes in the shoot apex of three apple dwarfing rootstocks (T337, Pamajul and JM7) and three common rootstocks (Malus prunifolia, M. micromalus and M. hupehensis) were compared by RT-qPCR. [Results] A total of 13 apple β-tubulin sequences were identified from the apple genome. The lengths of these 13 apple β-tubulins were from 444 aa to 450 aa, and the molecular weights ranged from 49.92 ku to 50.46 ku. The 13 apple β-tubulin genes were randomly distributed on 11 apple chromosomes, and fragment replication events were the main factor attributed to the expansion of apple β-tubulin family genes. Furthermore, phylogenetic tree analysis revealed that apple β-tubulin family can be divided into 5 subfamilies: ClassⅠhad 6 members with nomenclature of MdTUB1 to MdTUB6, and MdTUB10 and MdTUB11 were classified into ClassⅡ. Except for ClassⅢhaving only one member of MdTUB9, ClassⅣand ClassⅤboth had 2 members with nomenclatures of MdTUB7 and MdTUB8, MdTUB12 and MdTUB13 separately. Multiple sequence alignments showed that the amino acid sequences of the apple β-tubulins were highly conserved at the N-terminus, but only displayed slight differences at the C-terminus, which was also corroborated by three-dimensional structure prediction of apple β-tubulin family proteins, suggesting that the C-terminus differences might correlate with posttranslational modifications. Gene structure analysis showed that all 13 apple β-tubulin family genes contained 3 exons and 2 introns, and the amino acid sequences contained 10 conserved motifs, indicating that the functions of apple β-tubulin family members were probably highly conserved. The cis-acting element analysis of the promoter region showed that the abscisic acid responsive element, the methyl jasmonate responsive element and the anaerobic induction element were intensively distributed in the promoters of apple β-tubulin family genes. Furthermore, apple β-tubulin family genes displayed certain tissue expression specificities in the column apple Runtai No.1 variety, for instance, MdTUB2, MdTUB6, MdTUB9, MdTUB10 and Md-TUB11 were highly expressed in the phloem and MdTUB3 and MdTUB5 were mainly expressed in the young leaves. The relative expression of MdTUB1, MdTUB4 and MdTUB12 in xylems, young leaves and stem tips were significantly higher than in mature leaves and phloem. MdTUB8 was widely expressed in the detected tissues except for mature leaves, and MdTUB7 was highly expressed in young leaves and stem tips. In addition, the expression of MdTUB13 in stem tips were significantly higher than that in other detected tissues. This suggested that different tissues may selectively express different apple β-tubulin family genes to facilitate their growth and development. Furthermore, we found that the expression of MdTUB4 in the three common rootstocks (M. prunifolia, M. micromalus and M. hupehensis) was significantly higher than that in dwarfing rootstocks (T337, Pamajul and JM7), suggesting that MdTUB4 may positively regulate apple dwarfing. However, the expression pattern of MdTUB12 displayed opposite so that the relative expression of MdTUB12 was significantly higher in dwarfing rootstocks, suggesting MdTUB12 might negatively participate in regulating apple dwarfing. Apart from the MdTUB4 and MdTUB12, similar expression patterns were not observed with other apple β-tubulin family genes. These results indicated that MdTUB4 and MdTUB12 might be the candidate β-tubulin dwarfing genes involved in regulating apple dwarfing. [Conclusion] A total of 13 β-tubulin family genes were identified from the whole apple genome. Different apple tissues may selectively express specific β-tubulin genes to facilitate its growth and development. Furthermore, the selective expression of β-tubulin family genes is highly correlated with apple dwarfing and MdTUB4 and MdTUB12 might be the key genes involved in regulating apple dwarfing. The results will provide a theoretical basis for further research on the regulatory functions of apple dwarfing by β-tubulin genes.